ANALISIS PROFIL MISKONSEPSI DAN KONSISTENSI KONSEPSI SISWA SMA PADA TOPIK SUHU DAN KALOR - Alfiani Alfiani (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Misconceptions is the concept used is not right but accompanied with data or facts that occurred. Misconceptions experienced by students will hamper the process of receiving new knowledge in students, so that would hinder the success of the students in the learning process. Student misconceptions can lead to students' conceptions inconsistent. Hence, misconceptions need to be identified early so teachers can determine appropriate learning methods. Preliminary study results show that many students who have misconceptions. For example, when the researchers asked the difference between heat and temperature, the student replied that temperature is the value of the heat. In addition the students a lot of inconsistent conception to a concept. Based on these problems then conducted research on the development of an essay test as an initial step in the development of diagnostic tests and the results can be used in the didactic analysis. This type of research is descriptive survey method in class XI students who have studied the temperature and heat. Results of the study can provide information for further research studies in the development of the design of didactic hypothesized to reduce misconceptions and improve the consistency of students' conceptions.Keywords: Misconception, consistency of students’ conceptions, heat and temperature.